2023
DOI: 10.3390/pathogens12010121
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Characterization of Carbapenem-Resistant Klebsiella pneumoniae Isolated from an Egyptian University Hospital

Abstract: Globally, Klebsiella pneumoniae (K. pneumoniae) has been identified as a serious source of infections. The objectives of our study were to investigate the prevalence of multidrug-resistant (MDR) K. pneumoniae in Tanta University Hospitals, Gharbia Governorate, Egypt; characterize their carbapenem resistance profiles; and identify their different capsular serotypes. We identified and isolated 160 (32%) K. pneumoniae from 500 different clinical samples, performed antimicrobial susceptibility testing, and then us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 61 publications
2
9
1
Order By: Relevance
“…In this study, we found a low incidence (5.77%) of CP-Kp isolates that coharbored bla NDM-1 and bla KPC . These ndings are in accordance with previous studies conducted in Egypt, which report a low incidence (11.29%) (7 out of 62 isolates) [17] or absence [16] of the bla KPC gene in their CP-Kp isolates. This suggests that KPC is less prevalent in our geographic area.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we found a low incidence (5.77%) of CP-Kp isolates that coharbored bla NDM-1 and bla KPC . These ndings are in accordance with previous studies conducted in Egypt, which report a low incidence (11.29%) (7 out of 62 isolates) [17] or absence [16] of the bla KPC gene in their CP-Kp isolates. This suggests that KPC is less prevalent in our geographic area.…”
Section: Discussionsupporting
confidence: 92%
“…These ndings are in line with other studies conducted in Egypt and other countries that reported the absence of these genes in their CP-Kp isolates [16,19]. However, in contrast to our ndings, some studies report a higher prevalence [17]. Here, we could not detect the presence of bla SPM in any isolate.…”
Section: Discussionsupporting
confidence: 87%
“…The absence of such a correlation was discussed by Candan and Aksöz 90 in a study from Turkey. Furthermore, the absence of a correlation between the carbapenemases and capsular serotypes was documented by an Egyptian study of Taha et al 91 . Although Albasha et al 92 .…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the absence of a correlation between the carbapenemases and capsular serotypes was documented by an Egyptian study of Taha et al 91 Although Albasha et al 92 found no association between antimicrobial resistance and virulence genes in K. pneumoniae isolated from Sudan, they identified a significant association between entB and bla NDM (p-value = 0.005).…”
Section: F I G U R Ementioning
confidence: 95%
“…Metallo β -lactamases (Class B) and oxacillinases (Class D) are considered the major contributors to carbapenem resistance [ 15 ]. In Egypt the most common carbapenemases are bla OXA followed by bla VIM and bla NDM [ 15 , 16 ]. The best way to overcome carbapenem resistance is to use combinations of carbapenem and β -lactamase inhibitors (BLI).…”
Section: Introductionmentioning
confidence: 99%